2018
DOI: 10.1007/s11096-018-0643-7
|View full text |Cite
|
Sign up to set email alerts
|

A dual intervention in geriatric patients to prevent drug-related problems and improve discharge management

Abstract: Background Drug-related problems (DRPs) endanger geriatric patients' safety. Especially a follow-up treatment with increased number of care transitions is a critical time for patients. Objective This study aimed at optimising medication therapy and the transfer of medication-related information to ambulatory care in geriatric rehabilitation patients. Setting German geriatric rehabilitation centre (GRC). Method A prospective, controlled intervention study was performed. Patients in the control group (CG) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…The results of this research showed that the median (IQR) for the rates of accepted interventions was 78.8% (22.3%), the median (IQR) for the rates of implemented interventions was 64.15% (16.85%), and the median (IQR) for the rates of solved DRPs was 76.99% (26.09%), suggesting the intervention ability of DRPs and also reflecting the important role of pharmacists in DRPs intervention. The interventions of DRPs have been conducted in a number of studies, and serious consequences of DRPs have been avoided through pharmacists' intervention ( Freyer et al, 2018 ; Ylä-Rautio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research showed that the median (IQR) for the rates of accepted interventions was 78.8% (22.3%), the median (IQR) for the rates of implemented interventions was 64.15% (16.85%), and the median (IQR) for the rates of solved DRPs was 76.99% (26.09%), suggesting the intervention ability of DRPs and also reflecting the important role of pharmacists in DRPs intervention. The interventions of DRPs have been conducted in a number of studies, and serious consequences of DRPs have been avoided through pharmacists' intervention ( Freyer et al, 2018 ; Ylä-Rautio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For many cases, additional clinical and/or patient-specific information is needed. The access to patientspecific information collected during a patient interview helps to detect adherence issues, medication use problems, knowledge gaps, and adverse drug reactions [18]. Since patients are often present when prescriptions are filled, they might be a reasonable source of information for the identification of DRPs after hospital discharge in the community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients are often present when prescriptions are filled, they might be a reasonable source of information for the identification of DRPs after hospital discharge in the community pharmacy. Conversely, for the detection of, for example, incorrect dosing according to organ dysfunction, a medication without documented indication, or a diagnosis without treatment, pharmacists need access to clinical patient information [18]. However, in some European countries and in most community pharmacies in Switzerland, clinical patient information is not routinely accessible by pharmacists [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations